The effects of Hominis Placenta extract on Melanin synthesis of B16 melanoma cells - Hyung-Sik Seo (Korean Pharmacopuncture Institute, 2006)
Objective : This research was carried out for the development of medicine for vitiligo treatment and focused on the effect of Hominis Placenta extract on Melanin synthesis of B16 melanoma cells. Methods : Acitivity of tyrosinase playing a vital role in synthesis of Melanin and the quantity of Melanin, which is the final product in cultured B16 melanoma cells, effects of Hominis Placenta extract were measured. Results : The results indicated that Hominis Placenta extract increased both the amount of Melanin and the activity of tyrosinase according to the concentration, and they also supported by western blot analysis. Conclusion : The results suggests that Hominis Placenta extract has an advantageous effect on the promotion of Melanin synthesis and will contribute to the development of vitiligo treatment through further related studies.